On Commuting Graph of Group Ring $Z_nS_3$ (Communications in Mathematical Research, 2021)
The commuting graph of an arbitrary ring $R$, denoted by $Γ(R)$, is a graphwhose vertices are all non-central elements of $R$, and two distinct vertices $a$ and $b$ are adjacent if and only if $ab = ba$. In this paper, we investigate the connectivityand the diameter of $Γ(Z_n S_3)$. We show that $Γ(Z_n S_3)$ is connected if and only if $n$ is not a prime number. If $Γ(Z_n S_3)$ is connected then diam $(Γ(Z_n S_3)) = 3$, whileif $Γ(Z_n S_3)$ is disconnected then every connected component of $Γ(Z_n S_3)$ must be acomplete graph with same size, and we completely determine the vertice set of everyconnected component.
Keywords: group ring; commuting graph; connected component; diameter of a graph.